Metodologia para avaliação de desgaste abrasivo em pás de rotor de bombas centrífugas de estação elevatória - Rodrigo Otávio Perea Serrano (2017)
The abrasion resistance and erosion resistance of the rotors will depend on the characteristics of the materials used in their manufacture, where the hardness of their surface will determine the resistance to penetration of the impacts received. Despite the particular care taken in the choice of pump manufacturing material, abrasive wear of the rotor is practically impossible to completely avoid. This work analyzes the wear of the centrifugal pump rotor blades, used in the Gross Water Infrastructure Station (EEAB) of sedimentary rivers of the Brazilian Amazon, due to the variation of the river sediment load of the river. The preliminary analysis of the wear of two real rotors showed a combination of direct impacts at the tip and at the base of the blades, wearing the bed by sliding, direct shock and erosion by sliding around the periphery. In this study the abrasive capacity of the sediments of the Acre river bed, Brazil, was analyzed in the wear of three different ferrous materials used in the manufacture of centrifugal pump rotors used in the collection of raw water. In order to determine the wear mode and the relationship of the material specific wear coefficient (K), as a function of the sediment concentration, a rotating ball abrasometer tests were carried out on SAE 8620 steel, nodular FoFo and gray FoFo, using as abrasive suspensions the concentrations of 1, 2, 3, 5 and 10 g / l of sediment in distilled water. The wear volume as a function of the relative velocity of the mixture (water + sediment) relative to the rotor blades was estimated mathematically. The results show that: i) The K did not present significant difference as a function of the variation of the FN (1, 2 and 3N) during the tests performed; ii) the wear tests showed the abrasive capacity of the sediments in different concentrations; iii) as expected, SAE 8620 steel was more resistant to abrasive wear than gray and nodular FoFo samples; iv) sediment concentration has an important effect on the behavior and the coefficient of wear; and v) the rotational control of the pump as a function of sediment concentration and river level showed evidence of a 30% reduction in wear.